Ketrampilan Asertif Dalam Menyapaikan Pendapat Tanpa Menyingung Orang Lain - Mochamad Azriel Nuruguhty; Muhammad Ridho Al Hafizh; Michael Ridwan Lelo; Tri Wardhana; Iskandar (Shofanah Media Berkah, 2025)
Assertiveness is the ability to express opinions honestly, firmly, and responsibly without offending or harming others. A lack of this skill often leads individuals to be passive or aggressive in communication, which can trigger interpersonal conflict. This study aims to examine the role of assertiveness in expressing opinions effectively and respectfully. The method used is a literature review of various scientific sources discussing assertiveness, interpersonal communication, and empathy. The results of the study indicate that assertive communication is characterized by the use of polite language, emotional control, and the ability to understand the perspective of the interlocutor. Assertiveness contributes to creating harmonious social relationships in various life contexts.